Metal-organic framework (MOF)/reduced graphene oxide (rGO) composite for high performance CO sensor - More, Mayuri S.; Bodkhe, Gajanan A.; Ingle, Nikesh N.; Singh, Fouran; Tsai, Meng-Lin; Kim, Myunghee; Shirsat, Mahendra D. (Solid-state electronics, 2023)
•synthesis of NiO- MOF and its composite with thermally reduced GO has synthesized by hydrothermal method.•Synthesized materials characterized with XRD, FTIR, Raman spectroscopy, UV–Visible spectroscopy, BET surface area method, AFM and I-V.•The chemirestive sensor was fabricated by shadow mask technique on copper coated electrodes and CO gas was tested in the chemirestive modality.•Synthesized composite detected CO well below OSHA PEL level with good response time (30 sec) and recovery time (70 sec). High performance gas sensors are urgently needed for the welfare of modern society. A challenge for sensors to detect analytes is its high response time. Herein, a carbon monoxide sensor has been fabricated using a NiO-based metal–organic framework(MOF)/reduced graphene oxide(rGO) composite. Synthesis of NiO-MOF and NiO-MOF/rGO were carried out by hydrothermal method. All the synthesized materials were multi parametrically tested by X-ray Diffraction (XRD), Fourier Transform Infrared spectroscopy (FT-IR), Raman spectroscopy, UV–visible spectroscopy, Atomic Force Microscopy (AFM), Field emission scanning electron microscopy (Fe-SEM), Current-Voltage characteristics (I-V), Brunauer-Emmett-Teller analysis (BET), etc. for their structural, spectroscopic, morphological, electrical, and surface properties respectively. The NiO-MOF/rGO based chemiresistive sensor fabricated on a glass substrate with a 100 µm gap through a shadow mask using an e-beam evaporator is stable up to 30 days and shows a selective response towards CO with excellent response and recovery, i.e. 30 s and 70 s respectively at 25 ppm.